Implementation of Online Learning Science Subjects on the Aspects of Creative Thinking Ability in State Junior High Schools in Seberang Ulu II Sub-district, Palembang - Fenny Fitriana; Saleh Hidayat; Astrid W. Sumah (Bioedusiana: Jurnal Pendidikan Biologi, 2021)
Simultaneous online learning is carried out at home after the issuance of the Circular of the Minister of Education and Culture Number 4 of 2020 to minimize the spread of the corona virus. Online learning is learning where all or part of the process is carried out online or online. This also has an impact on science lessons in junior high schools in Palembang City. In its application, it cannot be separated from the obstacles faced. This study aims to determine the implementation of online learning in science subjects in terms of creative thinking skills and the obstacles faced in implementing it. The research method used is descriptive qualitative. The research subjects were students of class VII and teachers at SMP Negeri 16 and SMPN 30 Palembang. The results showed that the implementation of online learning in science subjects in the aspects of creative thinking skills can still run well even though there are obstacles in its implementation, the results of online learning observations are aspects of creative thinking abilities where the four aspects of creative thinking abilities are carried out with the results of students being creative enough for aspects of fluent skills and flexible skills., creative students for aspects of original thinking skills and creative enough for detail thinking skills. Teachers' obstacles in implementing online learning, especially in fostering creative thinking processes, apart from network constraints, are also obstacles in making questions that foster creativity and stimulate student stimulus because students do not meet face to face. The constraints of students are not only the absence of a network, the absence of quotas, difficulty in answering questions due to lack of understanding of the material and lack of motivation to learn from students.